2023
DOI: 10.3847/2041-8213/ad0781
|View full text |Cite
|
Sign up to set email alerts
|

Discovery of X-Ray Polarization from the Black Hole Transient Swift J1727.8−1613

Alexandra Veledina,
Fabio Muleri,
Michal Dovčiak
et al.

Abstract: We report the first detection of the X-ray polarization of the bright transient Swift J1727.8−1613 with the Imaging X-ray Polarimetry Explorer. The observation was performed at the beginning of the 2023 discovery outburst, when the source resided in the bright hard state. We find a time- and energy-averaged polarization degree of 4.1% ± 0.2% and a polarization angle of 2.°2 ± 1.°3 (errors at 68% confidence level; this translates to ∼20σ significance of the polarization detection). This finding suggests that th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
15
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 56 publications
3
15
0
Order By: Relevance
“…The polarization degree (PD) grows with the system inclination and energy and can achieve ∼15%-20% at high energies if the medium is viewed nearly edge-on. The first IXPE data on the hard-state systems revealed that the polarization signatures are largely consistent with these expectations (Krawczynski et al 2022;Ingram et al 2023;Veledina et al 2023).…”
Section: Introductionmentioning
confidence: 53%
See 2 more Smart Citations
“…The polarization degree (PD) grows with the system inclination and energy and can achieve ∼15%-20% at high energies if the medium is viewed nearly edge-on. The first IXPE data on the hard-state systems revealed that the polarization signatures are largely consistent with these expectations (Krawczynski et al 2022;Ingram et al 2023;Veledina et al 2023).…”
Section: Introductionmentioning
confidence: 53%
“…The MAXI monitoring of Swift J1727.8-1613 up to the new IXPE observation is summarized in Figure 2. The plot serves as an updated version of Figure 1 in Ingram et al (2023) and Veledina et al (2023) with slight variations due to the enhanced data selection, subtracting the region around GX 9+9.…”
Section: Maximentioning
confidence: 99%
See 1 more Smart Citation
“…As reported in the IXPEOBSSIM notes 57 and Veledina et al (2023), the polarization obtained by the PCUBE algorithm, when using the gray filter, does not properly account for the telescope response matrices at low energy. In particular, an overestimate of the polarization below 3 keV is observed with respect to the one obtained by the more solid XSPEC (Arnaud 1996) spectropolarimetric analysis, which properly considers the response matrices of the instrument at low energy.…”
Section: Polarimetric Analysismentioning
confidence: 97%
“…In particular, the 4% polarization observed for the archetypal BHXRB Cyg X-1 (Krawczynski et al 2022), parallel to the radio jet, constrained the geometry of the hot corona responsible for the power-law emission in the hard state, to be extended perpendicular to the jet direction (see Done et al 2007, for detailed descriptions of the different X-ray states). IXPE monitored the polarization properties of the recently discovered BH binary candidate, Swift J1727.8−1613, throughout its state transition from a hard to a soft state, suggesting that the Comptonizing corona extends over the disk, similar to the case of Cyg X-1 (Veledina et al 2023a;Ingram et al 2023). In the disk-dominated spectral states of LMC X-1, LMC X-3, and 4U 1957+115, IXPE observations indicate that the polarization measurements are consistent with the standard geometrically thin, optically thick accretion disks (Marra et al 2023;Podgorný et al 2023;Svoboda et al 2024).…”
Section: Introductionmentioning
confidence: 99%